Hubungan Komunikasi Perawat Dan Dokter Dengan Kinerja Perawat Perioperatif - Margareta Linda Puji Rahayu; Idawati Manurung; Merah Bangsawan; Yuni Astini (Malahayati Nursing Journal, 2022)
ABSTRACT Nurses and doctors really expect good collaboration in their daily work and this shows strong interprofessional interaction and collaboration. Until now, the communication between nurses and doctors has not reached a good level. The purpose of this study was to determine the relationship between nurse and doctor communication with perioperative nurse performance.  The research design was cross-sectional, quantitative analytic using total sampling technique, namely perioperative nurses 60 respondents at Yukum Medical Center Hospital, Lampung 2021. Statistical test with chi square test. The results of this study indicate that the average value of nurse and doctor communication and the average performance of nurses, were good, there was a relationship between nurse-doctor communication with nurse performance, with a p value of 0.00, with  OR,  45. In conclusion, there was  relationship between nurse-physician communication with perioperative nurse performance. More better communication nurse-doctor, more opportunities for better nurse performance. Good communication between nurses and doctors will provide a good working atmosphere and this will further improve the performance of nurses. Suggestions, improvement of nurse doctor communication is done by prioritizing verbal and direct communication. Communication via telephone and social media should only be supportive and of an emergency nature and immediately followed up with direct verbal communication. Improved non-verbal communication in interprofessional collaborative practice can be enhanced by application of integrated patient progress records or documentation. Keywords: Communication, Nurse, Doctor, Performance ABSTRAK Perawat dan dokter sangat mengharapkan kerjasama yang baik dan dalam kerja sehari-hari dan ini menunjukkan interaksi dan kolaborasi antar interprofesioanl yang kuat. Komunikasi antara perawat dan dokter sampai saat ini belum sampai taraf yang baik. Tujuan dari penelitian ini mengetahui hubungan komunikasi perawat dan dokter dengan kinerja perawat perioperatif. Desain penelitian analitik crosssectional, kuantitatif dengan menggunakan teknik total sampling, yaitu perawat perioperatif 60 responden di Rumah Sakit Yukum Medical Center, Lampung 2021. Uji statistika dengan uji chi square. Hasil penelitian ini menunjukan rata-rata nilai komunikasi perawat dan dokter baik dan rata-rata kinerja perawat, ada hubungan antara komunikasi perawat-dokter dengan kinerja perawat, dengan nilai p value 0.00, dengan OR 45. Kesimpulan, ada hubungan antara Komunikasi perawat-dokter dengan kinerja perawat perioperatif. semakin baik komunikasi, semakin membuat peluang kinerja perawat baik. Komunikasi yang baik antara perawat-dokter akan memberi suasana kerja baik dan ini akan semakin meningkatkan kinerja perawat. Saran, perbaikan komunikasi perawat dokter dilakukan dengan lebih memprioritaskan komunikasi verbal dan langsung. Komunikasi melalui telepon dan media sosial sebaiknya hanya penunjang dan bersifat darurat dan segera ditindaklanjuti dengan komunikasi verbal secara langsung. Peningkatan komunikasi dalam non verbal dalam praktik kolaborasi interprofesional dapat ditingkatkan dengan penerapan catatan perkembangan pasien terintegrasi atau dokumentasi. Kata Kunci: Komunikasi, Perawat, Dokter, Kinerja